Analyzing Factors That Influence the Behavior Intention of Consumer in Purchasing the Surabaya Apartment - Tika Dwi Septiani; Satria Fadil Persada (Institut Teknologi Sepuluh Nopember, 2020)
The supplies of apartments in Surabaya keep increasing, which was predicted from 2018 to at least 2022. However, this supplies were contradicted with the demand from market, which is stagnant or decreased. The present research tries to measure the consumers' behavior intention towards the purchasing apartment. The well famous Theory of Planned Behavior (TPB) is used in this research as the measurement model. Furthermore, the TPB is extended with several factors. The extended TPB consists of seven factors namely: Attitude (ATT), Subjective Norms (SN), Perceived Behavior Control (PBC), Perception (P), Lifestyle (L), and the Behavior Intention (BI). Five hypotheses are proposed. The analysis on this research is confirmatory factor analysis (CFA) with structural equation model (SEM). The factors are instrumented through questionnaires. The questionnaires are distributed through offline and online sample with purposive sampling method. In more detail, the sampling will be taken from marketing events, brokers, and building management and the 300 respondents are targeted. The expected result from this research can be used as references for developers, consumers, and brokers in order to enhance the knowledge regarding the consumers' perception. From the results of the analysis of several factors from the Extended Theory of Planned Behavior mentioned above, it is known that the factors that are proven to influence consumer behavior intentions when making apartment purchases are 3 factors including the following: Attitude (ATT), Perception (P) and Lifestyle (L) while two other factors Subjective Norms (SN) and Perceived Behavior Control (PBC) are proven not to influence consumer behavior intentions when making apartment purchases